Wood anatomy of Ribes magellanicum (Grossulariaceae) - Pujana, Roberto Roman (2008)
Wood anatomy description of Ribes magellanicum Poir. is given including specimens of itstwo subspecies. This is the first detailed secondary xylem study of a species included in the South andCentral American subgenus Parilla Jancz. Wood anatomy of R. magellanicum shows the followingtypical anatomical features cited for northern hemisphere Ribes L.: small vessels, rays of two distinctsizes and scalariform perforation plates.